Religion und Vernunft – Ein Widerstreit?: Glauben in der säkularen Gesellschaft. Vadian Lectures Band 4 - Meier Kressig, Marcel; Lindenau, Mathias (transcript, 2018)
What role does religion play in the secular society? How do faith and science, religion and reason relate to each other today? What part does religion play in ethical issues?